Simplify (1+cotθ+tanθ)(sinθcosθ)sec3θcosec3θ(1+cotθ+tanθ)(sinθcosθ)sec3θcosec3θ


Answer:

sin2θ cos2θsin2θ cos2θ

Step by Step Explanation:
  1. (1+cotθ+tanθ)(sinθcosθ)sec3θcosec3θ=(1+cosθsinθ+sinθcosθ)(sinθcosθ)(secθcosecθ)(sec2θ+secθ×cosecθ+cosec2θ) [Since, a3b3=(ab)(a2+ab+b2]=(sinθ cosθ+cos2θ+sin2θsinθ cosθ)(sinθcosθ)(1cosθ1sinθ)(1cos2θ+1sinθ cosθ+1cos2θ) [Since, secθ=1cosθ and cosecθ=1sinθ]=(1+sinθ cosθsinθ cosθ)(sinθcosθ)(sinθcosθ)(sin2θ+sinθ cosθ+cos2θ)(sinθ cosθ)(sin2θ cos2θ)=(1+sinθ cosθ)(sinθcosθ)(sin3θ cos3θ)(sinθ cosθ)(sinθcosθ)(1+sinθ cosθ)=sin2θ cos2θ

You can reuse this answer
Creative Commons License